Spin-orbit torque opposing the Oersted torque in ultrathin Co/Pt bilayers - Skinner, T.D.; Wang, M.; Hindmarch, A.T.; Rushforth, A.W.; Irvine, A.C.; Heiss, D.; Kurebayashi, H.; Ferguson, A.J. (American Institute of Physics, 2014)
Current-induced torques in ultrathin Co/Pt bilayers were investigated using an electrically driven ferromagnetic resonance technique. The angle dependence of the resonances, detected by a rectification effect as a voltage, was analysed to determine the symmetries and relative magnitudes of the spin-orbit torques. Both anti-damping (Slonczewski) and field-like torques were observed. As the ferromagnet thickness was reduced from 3 to 1nm, the sign of the sum of the field-like torque and Oersted torque reversed. This observation is consistent with the emergence of a Rashba spin orbit torque in ultra-thin bilayers.